Freedom, God, and worlds - Almeida, Michael J. (Oxford : Oxford University Press, 2013)
Michael J. Almeida presents a bold new defence of the existence of God. He argues that entrenched principles in philosophical theology which have served as basic assumptions in apriori atheological arguments are in fact philosophical dogmas. Almeida argues that not only are such principles false - they are necessarily false.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: God -- Proof; Philosophical theology